Al-Lughah al-‘Arabīyah fī Indūnīsīyā: Dirasah Taḥlilīyah ‘an Taṭawwurātihā wa Mushkilāt Ta’līmihā - Muhaiban, Muhaiban (Studia Islamika, 2006)
Arabic teaching in Indonesia started when Islam was introduced to this country in the 7th-8th Century. At that time Arabic was given merely for religious teachings and to teach student to read the HoIy Qur'an, say prayers, and read and understand religious books also known as "the yellow books". Those kinds of teachings were conducted in mosques, Moslem home, and religious schools. During the long period in history, Arabic teaching promoted the Arabic language into an important position in the cultural expressions of various ethnic groups in Indonesia. Arabic script was once also more prominent than the Latin alphabet in the written tradition in Indonesia.DOI: 10.15408/sdi.v13i1.577